Investigation of Factors Affecting Frequency of Intestinal Parasites in Primary School Students in an Urban Region in Turkey - Arıkan, İnci; Gülcan, Aynur; Dıbeklıoğlu, Saime Ergen (Central European journal of public health, 2016)
AIM: The aim of the study was to determine the incidence of intestinal parasitic diseases (IPD) and associated factors in primary school students and to assess the knowledge and practices of mothers about these diseases. METHODS: This is a cross-sectional study carried out in January-March 2014 in 471 students aged 5-11 years, studying at 3 schools randomly selected from the city centre regions with different socioeconomic levels. Stratified sampling method was used in the present study and the data were collected in two stages. In the first stage, parents were informed about the study and pre-prepared questionnaire forms were used to collect the data about the students and parents. In the second stage, laboratory analyses of collected stool samples were performed. RESULTS: The total prevalence of IPD was 18.3%, it was higher in the primary school located in a region with a lower socioeconomic level compared to other two schools (27.6% vs. 14.4%, and 10%, respectively). Most commonly detected parasite was E. vermicularis (12.1%). The prevalence of IPD was not associated with the classroom, gender, number of siblings, and the use of purified drinking water at home, while it was found to decrease with the increasing maternal education level. The maternal knowledge level score was 12.01±4.29 vs. 13.41±3.94 in students with and without IPD, respectively. With regard to the methods used to treat IPD, 23% of the mothers reported that they are using conventional methods. CONCLUSION: The health education programmes about the associated risk factors are of great importance for early detection and treatment of childhood parasitic infections.
Keywords: Feces; students; Turecko; Cross-Sectional Studies; Prevalence; Incidence; traditional practices; průzkumy a dotazníky; mužské pohlaví; prevalence; Turkey; incidence; průřezové studie; parazitární nemoci střev; dítě; Child; Child, Preschool; městské obyvatelstvo; ženské pohlaví; feces; předškolní dítě; Humans; Surveys and Questionnaires; intestinal parasitic diseases; Urban Population; Intestinal Diseases, Parasitic; Female; lidé; Male